Bronchoscopic Local Nd:YAG Laser Hyperthermia in the Treatment of Lung Cancer. Issue 3 (1995) - Ono, Ryosuke
Abstract : Between March 1989 and July 1990, 13 patients with tracheobronchial cancer were treated by laser hyperthermia at the National Cancer Center Hospital. A complete response was achieved in 9 patients (with 9 carcinoma lesions), with no evidence of local recurrence on follow-up ranging from 4 to 29 months. Four patients had a partial response, requiring alternative therapy. The surface area of the lesions showing complete response was less than 3 cm 2 . These lesions had a superficial appearance by bronchoscopic observation. Our experience suggests that laser hyperthermia may be a useful alternative to surgical resection in patients with small localized tumors confined within the tracheobronchial wall.